PERLINDUNGAN ANAK YANG DITANGKAP OLEH MILITER ASING DI NEGARA KONFLIK - Faisal Riza (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
The presence of children in armed conflict is not a rare case and cannot be avoided. Therefore, the protection of children is needed because of the age of them are still young and need a care, protection, and affection more than families and people who are nearby. A child who was captured by a foreign army in a conflict country, a reality that is bitter and depressing. Children are part of the civilian population must be protected, as stated in Article 24 of Geneva Convention IV which ensures that the warring factions will take the necessary actions for children under fifteen years old, children orphaned separate from his family because of the war, would not be left alone. These children get the protection, maintenance, and assistance in the implementation of worship and education. This convention ensures that children will remain protected in armed conflicts. The results showed that children who carried out the arrest of foreign military in armed conflict is a war crime that should not be done, because the children were arrested will undergo traumatic and it took a long time to recover.